Enzyme-Linked Immunosorbent Assay (ELISA): A Narrative Literature Review - Maya Chandra Dita (Natural Sciences Engineering and Technology Journal, 2021)
Enzyme immunoassay (EIA) and enzyme-linked immunosorbent assay (ELISA) are both widely used as diagnostic tools in medicine and as quality control measures in many industries. This literature review was aimed to describe enzyme linked immunosorbent assay in practical. ELISA has been the system of choice when testing soluble antigens and antibodies. EIA/ELISA uses the basic immunological concept of antigen binding to specific antibodies, which allows the detection of small amounts of antigens such as proteins, peptides, hormones or antibodies in fluid samples. In all protocols, solid-phase reagents are incubated with secondary or tertiary reactants covalently coupled with the enzyme. The unbound conjugate is washed and a chromogenic or fluorogenic substrate is added. In conclusion, EIA / ELISA is a powerful method not only for general biomedial research but also as a diagnostic tool. This procedure allows the detection of all types of biological molecules at very low concentrations and quantities. Despite their limitations, EIA/ELISA remains an important tool in both clinical and basic research, and in clinical diagnosis.